Ultrasonic spot welding of magnesium alloy to titanium alloy. (1st January 2017) - Ren, Daxin; Zhao, Kunmin; Pan, Min; Chang, Ying; Gang, Song; Zhao, Dewang
Abstract: This research explores the joining between dissimilar alloys (magnesium alloy and titanium alloy) by ultrasonic spot welding. The tensile shear test shows that the joint strength increases with energy input. The fracture initiates inside magnesium alloy, indicating a high joining strength at the weld interface. Banded grain-refinement is found at the interface on the magnesium alloy side, neither transition layer nor inter-metallic compound layer is identified though. The interfacial temperature exceeds the temperature range for liquefying magnesium alloy. The precipitated aluminum from the liquid-phase magnesium alloy plays a bridging role in ultrasonic welding of magnesium alloy to titanium alloy. Graphical abstract: